Contributions of Sexual and Reproductive Health Knowledge to Adolescent Pregnancies among Students in Kitui Township, Kitui County - Y Otsyula; E Wekesa; C Kinanga (Journal of Sociological Research, 2024)
Teenagers hold the future of society in terms of the provision of societal functions differentiated by their gender roles and parity. Consequently, the excellence of teenagers places society in a better sustaining status. The successful transition of teenagers to adulthood depends on mentorship. Research reports that the female gender is prone to a pathway with more challenges than male teenagers. Girls are challenged with sexual reproductive health and pregnancy issues, which may eventually disorient their social, economic cultural and health outcomes. In light of this, the importance of establishing the teenage pregnancy landscape and the associated health knowledge could not be underscored. This research, therefore, sought to determine the contributions of sexual and reproductive health knowledge to adolescent pregnancies among students in Kitui township, Kitui County. The study involved a target population of 467 from which a sample size of 140 was enumerated using a mixed-method cross-sectional research design. Ten (10) female teachers were involved in the study as key informants. The data collected using FGDs, questionnaires and key informant guides show that over half (66%) of the girls’ population was knowledgeable and the larger source of their knowledge was teachers. The study findings give the current teenage pregnancies landscape and can be used for regulatory and advisory purposes by bodies, which deal with girl child welfare like UNICEF.